2020
DOI: 10.1021/acsomega.0c05078
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Porous Spherical Reduced Graphene Oxide and Its Application in Immobilized Pectinase

Abstract: Pectinase is widely used in juice production, food processes, and other fields. However, owing to poor stability, free pectinase is difficult to separate from a substrate after hydrolysis and cannot be reused, and thus its industrial use is limited. Immobilized pectinase can solve these problems well. We prepared a carrier material of immobilized enzyme, which is called porous spherical reduced graphene oxide (rGO) with a rich pore structure, large specific surface area, strong hardness, and good biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The discovery of graphene [1] changed the scenario of the research world of nanomaterials. Graphene and its derivatives have become one of the most fascinating and hottest research topics in the empire of carbon nanomaterials [1][2][3][4][5][6][7][8][9], because of their versatile properties like high surface area, high mechanical strength, and excellent electrical and thermal conductivities, and promising applications in the field of material science and engineering, including energy storage, catalysis, drug delivery, sensing and biosensing, and water treatment [10][11][12][13][14][15][16][17][18] Various methods have been employed to produce graphene and its analogue, reduced graphene oxide (rGO). In particular, chemical reduction of exfoliated graphene oxide (GO) is efficient and advantageous in the large-scale production of rGO, because high-quality rGO with a relatively lower oxygen content can be obtained at a low cost in a short time [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of graphene [1] changed the scenario of the research world of nanomaterials. Graphene and its derivatives have become one of the most fascinating and hottest research topics in the empire of carbon nanomaterials [1][2][3][4][5][6][7][8][9], because of their versatile properties like high surface area, high mechanical strength, and excellent electrical and thermal conductivities, and promising applications in the field of material science and engineering, including energy storage, catalysis, drug delivery, sensing and biosensing, and water treatment [10][11][12][13][14][15][16][17][18] Various methods have been employed to produce graphene and its analogue, reduced graphene oxide (rGO). In particular, chemical reduction of exfoliated graphene oxide (GO) is efficient and advantageous in the large-scale production of rGO, because high-quality rGO with a relatively lower oxygen content can be obtained at a low cost in a short time [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Figure presents together the transmittance FT-IR spectra of bare and encapsulated K 2 FeO 4 . In the case of the former (Figure a), a primary peak appeared at 808 cm –1 along with a shoulder peak at 780 cm –1 , which was the characteristic peak of FeO 4 . In the case of the latter (Figure b), the spectrum showed the characteristics peaks of the shell materials. The characteristic peak at 1100 cm –1 arose from ethyl cellulose, and those centered around 2916, 1471, and 720 cm –1 belong to the stretching and bending vibrations of paraffin wax .…”
Section: Resultsmentioning
confidence: 95%
“…The emissions from it largely impact water toxicity and could give cancerous effects on humans . Gao et al suggested that l -ascorbic acid (vitamin C) is an excellent alternative for hydrazine in the reduction of GO. , Unlike hydrazine, l -ascorbic acid is environmentally friendly and does not cause any ill effects in human respiratory organs. , Zengin Kurt et al compared the effects of several reducing agents extracted from plants such as cloves, white mulberry, black cumin seed, blackthorn, dark grape, and rosehip on the synthesis of PG materials. However, all these relatively green techniques are only applicable to the synthesis of PG from a GO precursor.…”
Section: Introductionmentioning
confidence: 99%
“…In some variations, the reducing agents are first mixed with graphite powder, followed by ball-milling to obtain GO, which is then further reduced to RGO [71]. Also, few groups prepared graphene (or RGO) from graphite using L-ascorbic acid and L-arginine as reducing agents, which are mild, nontoxic, environmentfriendly alternatives for conventional reducing agents [75][76][77][78][79].…”
Section: Green-chemical Reduction Of Graphene Oxidementioning
confidence: 99%